Consumption insurance among Blacks and Whites - Costanza Naguib (University of Bern, Department of Economics, 2022)
We document relevant racial differences in the degree consumption insurance against shocks: Blacks appear to be less insured. We probe these results by performing a double/debiased lasso estimation of the treatment effects of a health shock, and we find that such effects are both larger and more long-lasting for Blacks than for Whites. With the help of a toy model, we show that, having a lower life expectancy, Blacks save less and, as a consequence, are less insured than Whites against both income and health shocks.
Keywords: E21; D12; C3; 330; Consumption; Insurance; Inequality; Savings; Life Expectancy